The linkages between weather and the stock market performance / Filiyvia Freddie Luji - Freddie Luji, Filiyvia (2015)
This study basically investigates the linkages between stock market performance and the weather variable such as sunny, cloudy and raining. These findings will show that weather effect really exist in stock market. This study will provides useful outcomes to all people especially to investor to know the investment activity.